EFFECT OF PROGRESSIVE MUSCLE RELAXATION THERAPY TO DECREASE BLOOD PRESSURE OF HYPERTENSION PATIENTS AT WORKING AREA OF PUSKESMAS KOTA UTARA IN GORONTALO CITY - Ratnawati (International Interdisciplinary Conference on Sustainable Development Goals, 2019)
Hypertension is a silent killer where symptoms can vary between individuals and are almost the same as other disease symptoms. Hypertension is the highest disease experienced by the elderly with prevalence 54.9 % on age 55-64 years of age 54.9, 57.6 % on ages 65-74, and 63.8 % on age over 75. This research aimed to find the influence of progressive muscle relaxation therapy to decrease blood pressure of hypertension patients in working area of Puskesmas Kota Utara of Gorontalo City. This type of research used in this study is Quasi Experiment Design with One Group Pretest-Posttest design. Data analyzed through Wilcoxonsign rank statistic test, with 30 sample. Independent variables wasprogressive muscle relaxation therapy and dependent variable was blood pressure. The results of data analysis using Wilcoxon sign rank test with a significant level α = 0.05 with p value = 0.000 which means that progressive muscle relaxation techniques have significance influence in reducing blood pressure in patients with hypertension in the working areaof Puskesmas Kota Utara in Gorontalo City